Calcineurin-mediated Dephosphorylation of Synaptotagmin VI Is Necessary for Acrosomal Exocytosis - Castillo Bennett, Jimena Victoria (2010)
Regulated secretion is a fundamental process underlying thefunction of many cell types. In particular, acrosomal exocytosisin mammalian sperm is essential for egg fertilization. In general,exocytosis is initiated by a cytosolic calcium increase. In thisreport we show that calcium affects several factors duringhuman sperm acrosomal exocytosis. By using an antibody thatspecifically recognizes synaptotagmin VI phosphorylated at thepolybasic region of the C2B domain, we showed that a calciumdependentdephosphorylation of this protein occurred at earlystages of the acrosomal exocytosis in streptolysin O-permeabilizedsperm. We identified the phosphatase as calcineurin andshowed that the activity of this enzyme is absolutely requiredduring the early steps of the secretory process. When added tosperm, an inhibitor-insensitive, catalytically active domain ofcalcineurin was able to rescue the effect of the specific calcineurininhibitor cyclosporin A. This same domain dephosphorylatedrecombinant synaptotagmin VI C2B domain, validatingthis protein as a new substrate for calcineurin. Whensperm were treated with catalytically active calcineurin beforestimulation, exocytosis was inhibited, an effect that was rescuedby the phosphomimetic synaptotagmin VI C2B-T418E,T419Emutant domain. These observations indicate that synaptotagminmust be dephosphorylated at a specific window of time andsuggest that phosphorylated synaptotagmin has an active role atearly stages of the acrosomal exocytosis.